Meio condicionado de macrófagos ativados por polissacarídeos sulfatados da alga parda Dictyota caribaea inibe a proliferação de melanoma metastático In vitro - Assef, Alexia Nathália Brígido (2017)
Cancer refers to a set of diseases related to uncontrolled proliferation and invasion of neoplastic cells into distant tissues. The tumoral tissue is complex and consists of several non-tumor cells that contribute, together with the tumor cells, to the formation of the tumor microenvironment (MIT). MIT favors the growth and development of the tumor and increase the aggressiveness of the disease. Among the non-tumor cells present in MIT, macrophages (MΦ) have prominent role. MΦ have high phenotypic plasticity, and may show anti-tumor action when activated classically (M1 phenotype) or pro-tumor, when tumor-associated MΦ undergo alternative activation (M2-like phenotype). TAMs are often related to a worse prognosis for the patient. Modulation from M0 MΦ (unstimulated) to M1 or re-education from TAM to M1 are strategies aimed at assisting in the treatment of malignant tumors. Sulfated polysaccharides (SP) from algae can act as modifiers of the biological response by regulating the activation of MΦ and potentiate the immune response against tumor cells. The objective of this work was to evaluate the immunostimulatory and antitumor potential of sulfated polysaccharides extracted from brown algae Dictyota caribaea (DCA) in vitro. Samples of DCA and conditioned medium of macrophage stimulated with DCA (CM) were initially evaluated for cytotoxicity in murine metastatic melanoma (B16-F10 cell line) by the SRB assay and activation of murine macrophages (RAW264.7 cell line) by the Griess assay. Although samples, including crude extract and fractions, were not cytotoxic, all of them activated the MΦ. Additionally, the supernatants of macrophages treated with DCA (CM DCA) were able to inhibit B16-F10 cells growth approximately 25%. The DCA F9 fraction was chosen for additional studies using CM DCA F9 due to their high yield (~40%) and better antiproliferative effect among the other fractions. In addition to increasing nitric oxide production, treatment of macrophages with DCA F9 also increased the release of TNF-α and IL-10 cytokines as measured by ELISA. Treatment of melanoma with CM DCA F9 caused a reduction on cell counting and induced morphological changes without compromising membrane integrity. In relation to the morphology, it was observed an increasing of the population percentage of shrink cells (~10%) and granularity cells (~15%). CM DCA F9 treatment also changed B16-F10 cell cycle profile. It decreased the G2/M phase. Since nitrite did not inhibit the growth of B16 F10, the antiproliferative effects observed are due to other cytotoxic substances produced by RAW264.7, e.g. TNF-α. When associated with the chemotherapeutic doxorubicin (DOX), DCA F9 but not CM DCA F9, potentiated tumor cell inhibition in vitro. In conclusion PS of D. caribaea activated MΦ for anti-tumor phenotype. Further studies are needed to improve phenotypic characterization of MΦ, as well as the antitumor effect and respective pathways related to these effects.